Dishwashing practice and its determinants among food handlers in food and drinking service establishments in Dessie City and Kombolcha Town, Northeastern Ethiopia - Moges, Mekonnen; Adane, Metadel; Adane, Balew; Kassaw, Genanew Mulugeta; Teym, Abraham; Yirdaw, Getasew; Kumlachew, Lake; Ayele, Agernesh; Bewket, Yenewa; Gebrehiwot, Mesfin (Frontiers in Food Science and Technology, 2025)
BackgroundFood contamination arising from various sources, including the use of dirty utensils, is a significant global and national public health concern. Proper dishwashing practices are critical in mitigating this issue by ensuring food safety, yet their effectiveness depends on various factors. In settings with high food safety concerns and limited measurement capabilities, addressing these factors is hindered by the paucity of research. To bridge this gap, this study proposes to evaluate the dishwashing practice employed by food handlers in food and drinking establishments and its determinants in Dessie City and Kombolcha Town, Northeastern Ethiopia.Methods and MaterialsAn institution-based cross-sectional study was done on 405 food handlers from 405 food and drinking establishments from 25 June 2022 to 25 August 2022 in Dessie City and Kombolcha Town. Data were collected by pre-tested semi-structured questionnaires and observational checklists. Multivariable (adjusted odds ratio) logistic regression analysis with a 95% confidence interval (CI) was used.ResultsMore than one-third of food handlers in Dessie City and Kombolcha Town food and drinking establishments lack adequate three-compartment dishwashing practices. Among those demonstrating inadequate practices, only one-third achieved an acceptable level of microbial load, ≤1 log CFU/cm2. Being widowed (adjusted odds ratio (AOR) = 5.92, 95% CI [1.78–19.68]), taking safety training (AOR: 3.08, 95% CI [1.61–5.64]), and having a favorable attitude (AOR: 4.81, 95% CI: 2.65–8.72) were determinants to having adequate three-compartment dishwashing practices. Furthermore, having detergents (AOR = 3.07, 95% CI [1.67–5.63]) and having a water storage tank (AOR: 5.55, 95% CI [2.73–11.283]) were determinants to having adequate three-compartment dishwashing practice.ConclusionTraining status, marital status, attitude, availability of detergent and a water storage tank or container, and number of customers visiting the food and drinking service establishments were contributor determinants for practicing three-compartment dishwashing adequately.